Crescimento, resposta fisiológica e qualidade de filé de juvenis de beijupirá (Rachycentron canadum) submetidos a diferentes densidades de estocagem - SILVA, Victor Andrade da (2013)
Stocking density is recognized as a critical factor in aquaculture, since high densities represent a potential source of chronic stress. This study investigated the effects of a chronic stressor, such as high stocking densities, on growth, physiological responses, and flesh quality of juvenile cobia (Rachycentron canadum) tested for a period of 42 days. The trial was conducted in a recirculating aquaculture system equipped with tanks of 70 L tanks. Cobia of 46.32 ± 0.22 g (mean ± SEM) were randomly distributed into three stocking densities (3.30 ± 0.02; 6.67 ± 0.03; 13.15 ± 0.16 g L-1), and three replicates. Treatment groups were nominally assigned as low density (LD; 5 fish/tank), medium density (MD; 10 fish/tank), and high density (HD; 20 fish/tank), respectively. Plasma concentrations of cortisol, osmolality and lactate were not affected by density levels, and values were according with those reported as basal for juvenile cobia. However, growth rate were influenced by density levels, in which weight gain and specific growth rate were significantly higher in the LD group. Drip loss did not differ among density groups. However, stocking density influenced the onset and development of rigor mortis. Our findings indicated that rearing juvenile cobia at the high densities negatively affected growth rate and flesh quality. Results suggest that juvenile cobia reared at the high densities were able to counteract stress. However, energy from the diet and/or body reserves was diverted from growth as a response to the elevated metabolic demand caused by stress. In this regard, juvenile cobia should be maintained at a final biomass up to approximately 15 kg m-3 to ensure a maximal growth rate and an improved final product quality. To our knowledge, this is the first report assessing the influence of a chronic stressor on both physiological responses and flesh quality parameters in cobia. This may provide information to the advancement of cobia aquaculture, leading to improvements in fish welfare, final product quality and increased productivity.